Cordial and Total Cordial Labeling of Corona Product of Paths and Second Order of Lemniscate Graphs - Ashraf ELrokh; Mohammed M. Ali Al-Shamiri; Shokry Nada; Atef Abd El-hay (Journal of Mathematics)
A simple graph is called cordial if it admits 0-1 labeling that satisfies certain conditions. The second order of lemniscate graph is a graph of two second order of circles that have one vertex in common. In this paper, we introduce some new results on cordial labeling, total cordial, and present necessary and sufficient conditions of cordial and total cordial for corona product of paths and second order of lemniscate graphs.